Four new diterpenoid alkaloids from Delphinium elatum. (September 2016) - Wada, Koji; Asakawa, Erika; Tosho, Yoshie; Nakata, Ayako; Hasegawa, Yuko; Kaneda, Kyousuke; Goto, Masuo; Yamashita, Hiroshi; Lee, Kuo-Hsiung
Graphical abstract: Four new C19 -diterpenoid alkaloids, melpheline (1 ), 19-oxoisodelpheline (2 ), N -deethyl-19-oxoisodelpheline (3 ), and N -deethyl-19-oxodelpheline (4 ), were isolated from Delphinium elatum cv. Pacific Giant. Highlights: New diterpenoid alkaloids were isolated from Delphinium elatum cv. Pacific Giant. Melpheline is an unusual diterpenoid alkaloid with a 7, 8-dioxymethylene group. 19-Oxoisodelpheline is the first reported lycoctonine-type C19 -diterpenoid alkaloid with a 7, 8-dioxymethylene moiety and a 19-oxo group. Abstract: Diterpenoid alkaloids exhibit remarkable chemical properties and biological activities. Such compounds are frequently found in plants of the genera Aconitum, Delphinium, and Garrya. Several diterpenoid alkaloid components from Delphinium elatum cv. Pacific Giant and their derivatives exhibited cytotoxic activity against lung, prostate, nasopharyngeal, and vincristine-resistant nasopharyngeal cancer cell lines. Phytochemical investigations on the seeds of D. elatum cv. Pacific Giant led to the isolation of four new C19 -diterpenoid alkaloids, melpheline (1), 19-oxoisodelpheline (2), N -deethyl-19-oxoisodelpheline (3), and N -deethyl-19-oxodelpheline (4). The isolated alkaloids were elucidated by extensive spectroscopic methods including NMR (1D and 2D), IR, and MS (HRMS).